Digital Immortality in Palaeoanthropology and Archaeology: The Rise of the Postmortem Avatar - Caroline M. Wilkinson; Mark A. Roughley; Sarah L. Shrimpton (Heritage)
It has been proposed that we are entering the age of postmortalism, where digital immortality is a credible option. The desire to overcome death has occupied humanity for centuries, and even though biological immortality is still impossible, recent technological advances have enabled possible eternal life in the metaverse. In palaeoanthropology and archaeology contexts, we are often driven by our preoccupation with visualising and interacting with ancient populations, with the production of facial depictions of people from the past enabling some interaction. New technologies and their implementation, such as the use of Artificial Intelligence (AI), are profoundly transforming the ways that images, videos, voices, and avatars of digital ancient humans are produced, manipulated, disseminated, and viewed. As facial depiction practitioners, postmortalism crosses challenging ethical territory around consent and representation. Should we create a postmortem avatar of someone from past just because it is technically possible, and what are the implications of this kind of forced immortality? This paper describes the history of the technologically mediated simulation of people, discussing the benefits and flaws of each technological iteration. Recent applications of 4D digital technology and AI to the fields of palaeoanthropological and historical facial depiction are discussed in relation to the technical, aesthetic, and ethical challenges associated with this phenomenon.